2019
DOI: 10.1016/j.fsigss.2019.09.127
|View full text |Cite
|
Sign up to set email alerts
|

HERC2 (rs12913832) and OCA2 (rs1800407) genes polymorphisms in relation to iris color variation in Belarusian population

Abstract: To develop a specific predictive model for the forensic casework for the Belarusian population, we set up an investigation of the connection between candidate pigmentation SNPs and quantitatively measured eye color of individuals. 471 participants were genotyped for rs12913832 (HERC2) and rs1800407 (OCA2) using TaqMan approach. The obtained data were confirmed by sequencing. The SNP allele distribution in the target regions of the individuals under research was shifted to the G-alleles for both spots: 82% -rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Although the sample size was limited (n = 24), rs12913832 AA individuals of Norwegian ancestry had less brown eye colours (based on PIE-score) than individuals of non-northern European ancestry. The rs12913832 A allele is positively affecting transcription of OCA2 and has been shown to be strongly associated with dark iris colour [18,43]. However, a nonsynonymous mutation (A-allele) in rs1800407 is suggested to be a penetrance modifier of rs12913832, associated with lighter eye colour [19,30,44].…”
Section: Tablementioning
confidence: 99%
“…Although the sample size was limited (n = 24), rs12913832 AA individuals of Norwegian ancestry had less brown eye colours (based on PIE-score) than individuals of non-northern European ancestry. The rs12913832 A allele is positively affecting transcription of OCA2 and has been shown to be strongly associated with dark iris colour [18,43]. However, a nonsynonymous mutation (A-allele) in rs1800407 is suggested to be a penetrance modifier of rs12913832, associated with lighter eye colour [19,30,44].…”
Section: Tablementioning
confidence: 99%
“…This way of prediction can be helpful for individual identification in certain criminal investigations, and it is known as forensic DNA phenotyping (FDP) (Koops & Schellekens, 2008). However, the bulk of available studies on EVC genetics is mainly focused on European populations (Liu et al, 2009;Mengel-From et al, 2009;Shapturenko et al, 2019;Sulem et al, 2007;Walsh et al, 2012), and only more recently, the scientific community began to analyze this topic in admixed populations (Beleza et al, 2013;Edwards et al, 2015;Lloyd-Jones et al, 2017), especially from Latin America (Carratto et al, 2019(Carratto et al, , 2020(Carratto et al, , 2021Hohl et al, 2018;Marano et al, 2019;Palmal et al, 2021;Silva de Cerqueira et al, 2014). Considering that differences in the genetic pool of a population can influence phenotype predictions based on genotype information (Beleza et al, 2013;Carratto et al, 2019Carratto et al, , 2020Carratto et al, , 2021Frudakis et al, 2003;Popejoy & Fullerton, 2016;Sirugo et al, 2019), there is a need for these comprehensive studies in admixed populations.…”
Section: Introductionmentioning
confidence: 99%
“…LD haplotype containing these SNPs were also significantly associated with the two categories eye colors black/green iris pigmentation. These deviations provide an indication of the association with Shapturenko et al, (2019) 9 . A study in Saudi population 10 observed the SNP rs1800407 was not polymorphic in the Saudi population with the presence of the allele G. In this study, concluded the rs1800407 indicating of eye color with the rs12913832 because of the linkage disequilibrium coefficient between alleles of these SNPs strong associated with eye color.…”
Section: Discussionmentioning
confidence: 88%